R. M. Haig: Pioneer Advocate of Expenditure Taxation? - Wildasin, David E. (Journal of Economic Literature, 1990)
For more than a decade, there has been a great debate in the profession concerning the proper base for personal and business taxation. This debate has focused on the choice of the base versus the (or consumption) base. The concept of used in these debates is a comprehensive accretion measure often referred to as HaigSimons income, after the work of Robert M. Haig (1921) and Henry C. Simons (1938). This is the standard concept of income that has been used (with several variations) in tax policy analysis in the postwar period. However, it appears not to be widely recognized that, although Haig did ultimately settle on accretion income as the best feasible tax base, he definitely saw this as a second-best measure of true income. As will become clear, reexamination of Haig's famous article reveals that Haig actually felt that consumption expenditure would be a better measure of true income than accretion income, and he would have preferred a tax on this base-that is, he preferred what today would be called a consumption tax. He felt that